COVID‐19 in the pre‐pandemic period: a survey of the time commitment and perceptions of infectious diseases physicians in Australia and New Zealand. Issue 8 (6th August 2020) - Foley, David A.; Chew, Rusheng; Raby, Edward; Tong, Steven Y. C.; Davis, Joshua S.; ,
Abstract: Background: Infectious diseases (ID) physicians perform a pivotal role in directing the response to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Aim: To assess the impact of SARS‐CoV‐2 on workload and the perceptions of ID physicians regarding the national response in Australia and New Zealand in the pre‐pandemic. Methods: A survey of ID physicians in Australia and New Zealand was undertaken from 3 to 10 March 2020. Respondents were asked to estimate time spent on SARS‐CoV‐2‐related activities in February and report their agreement with statements on a 5‐point Likert scale ranging from 'strongly agree' to 'strongly disagree'. We also asked about the intended use of investigational agents. Results: There were 214 respondents (36% of 600 eligible participants). The median workload due to SARS‐CoV‐2‐related activities was 34% of one full‐time equivalent (interquartile range 18–68%). Less than a quarter (50, 23%) of respondents had experience managing cases, while 33% (70) had experience preparing during similar pandemics. Nevertheless, 88% (188/213) believed they were well informed when giving testing and management advice, and 45% (95/212) believed their national response was well coordinated. Additionally, 41% (88/214) were worried about becoming infected through occupational exposure. Over half (116, 54%) the respondents intended to use lopinavir/ritonavir in confirmed cases of COVID‐19 with severe disease. Conclusions: ID physicians spent a large proportion of time on SARS‐CoV‐2‐related activities. Increased staffing is required to avoid burnout. Importantly, ID physicians feel well informed when giving advice. A national body should be established to co‐ordinate response. Treatment efficacy trials are needed to clarify the utility of unproven treatments.